Analysis of Trends in Rainfall Changes Based on ERA5 Reanalysis Data as an Impact of Climate Change in Yogyakarta Province for the Period 1970-2019 - Aditya Prapanca; Hasibuan, Muhammad Ansori; Rafif Firjatullah; Desak Putu Okta Veanti (Tinta Emas Institute, 2023)
This study aims to analyse the trend of rainfall changes in Yogyakarta Special Region (DIY) Province during the period 1970-2019 based on ERA5 reanalysis data. The analysis method of this study involves the use of 50 years of ERA5 rainfall data with high spatial and temporal resolution. The data was processed using the Climate Data Operator (CDO) to obtain monthly average values in five specified periods. In Period I to II, there was an increase in rainfall of +8%, especially in 5 months ranging from 18% to 37%, while the other 7 months showed a downward trend. In Period II to III, rainfall decreased by -7%, mainly in 7 months ranging from 3% to 32%, while the other 5 months showed an increase. In Period III to IV, there was an even greater decrease in rainfall, reaching -8%, accompanied by a decrease in 9 months ranging from 2% to 58%, while the other 3 months showed an increase. In Period IV to V, there was again a significant increase of +12%, mainly during 10 months ranging from 2% to 97%, while the other 2 months showed a decrease. The increase in rainfall mainly occurs in certain time intervals, while the peak of rainfall tends to shift, indicating that climate change has occurred in Yogyakarta.